Impactos da estratégia de produto no canal de distribuição : estudo multicaso sobre o relacionamento entre a indústria avícola e o varejo - Pêgo, Luíza Santos (2009)
The strategy of the marketing channel can not be formulated as there was no other itens to be explored in the marketing strategy of the companies. The variable product was chosen among the other three from the marketing mix, as it is considered the activity essence of any industry. Three large areas can be highlighted as the ones more related to the marketing channel management: new product planning and development, product life-cycle and strategies related to the product management. The proposal of this work was to analyze how the interrelation between the product questions, previously quoted, and the domestic marketing channels management of the poultry industry affect their relationship with the retail link of the channel. This industry was chosen due to its importance to the national agribusiness, as a currency generator as well as to the internal market supplying. This research restricted to study the direct relationship between large companies and large retail trade operative in Brazil, not considering the wholesalers. As a research method, it was adopted the multiple case study in the poultry industry and the retail. In loco interviews were conducted with the directors of the product and marketing areas of the poultry industry and the commercial managers of the retailers. The interviews were conducted with the use of a semistructured questionnaire, validated by researchers of different areas. This research has identified that the relationship level between the poultry industry and the retail, in the three areas studied, is unsatisfactory for the involved parts. It was veriried that the new products planning an developing areas are the ones more affected by the lack of communication between the industry and the retail. In this way, the enterprises claim to more collaborative actions of their partners, in different areas, in order to begin a cooperation process between the parts. Although they pointed out this wish, both industry and retail have not shown being motivated to take any initiative in this way. This can be explained by, mainly, the market power of both actors exhibited during the final product negotiation.